2022
DOI: 10.48550/arxiv.2206.03406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling Modified Gravity and Massive Neutrinos with Intrinsic Shape Alignments of Massive Halos

Abstract: Two new diagnostics to break the dark sector degeneracy based on the intrinsic shape alignments of group/cluster size dark matter halos are presented. Using the snapshot data from a series of the DUSTGRAIN-pathfinder N-body simulations for the Planck ΛCDM cosmology and three f (R) gravity models with massive neutrinos (ν), we first determine the probability density functions of the alignment angles between the shape orientations of massive halos and the minor principal axes of the local tidal fields. The numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The DUSTGRAIN-pathfinder simulation project aimed at keeping track of 768 3 CDM particles of individual mass 8.1 × 10 10 h −1 M e under the influence of f (R) gravity in the presence of massive neutrinos (Giocoli et al 2018) For each of the four models, i.e., the ΛCDM and the three νCDM+f (R) gravity cosmologies, Lee et al (2022) identified the DM halos by applying the Rockstar algorithm (Behroozi et al 2013) to the snapshot data of the DUSTGRAINpathfinder simulations. From the Rockstar halo catalogs at z = 0, we extract the cluster-size distinct halos with M v 4.05 × 10 13 h −1 M e enclosing 500 or more DM particles within their virial radii r v .…”
Section: Physical Analysismentioning
confidence: 99%
“…The DUSTGRAIN-pathfinder simulation project aimed at keeping track of 768 3 CDM particles of individual mass 8.1 × 10 10 h −1 M e under the influence of f (R) gravity in the presence of massive neutrinos (Giocoli et al 2018) For each of the four models, i.e., the ΛCDM and the three νCDM+f (R) gravity cosmologies, Lee et al (2022) identified the DM halos by applying the Rockstar algorithm (Behroozi et al 2013) to the snapshot data of the DUSTGRAINpathfinder simulations. From the Rockstar halo catalogs at z = 0, we extract the cluster-size distinct halos with M v 4.05 × 10 13 h −1 M e enclosing 500 or more DM particles within their virial radii r v .…”
Section: Physical Analysismentioning
confidence: 99%
“…[168][169][170][171][172][173][174][175][176][177]), as well as related cosmological observables (see e.g. [178][179][180][181][182][183][184][185][186][187][188][189][190]).…”
Section: Introductionmentioning
confidence: 99%